SOCIAL-PHILOSOPHICAL FOUNDATIONS OF ENSURING ECOLOGICAL SECURITY IN UZBEKISTAN IN THE CONTEXT OF GLOBAL ECOLOGICAL PROBLEMS (American Journal of Research in Humanities and Social Sciences, 2026)
In the current era of globalization, environmental problems are one of the most pressing issues facing humanity. Excessive use of natural resources, rapid industrial development, urbanization processes, and disruption of the ecological balance are leading to an increase in global environmental threats. This article analyzes the socio-philosophical foundations of ensuring environmental security in Uzbekistan in the context of global environmental problems. The study highlights the essence of the concept of environmental security, the philosophical aspects of the relationship between man and nature, the importance of the concept of sustainable development, and the need to develop an ecological culture. The results of the study show that environmental education, environmental awareness, and environmental policy play an important role in ensuring environmental security in Uzbekistan.